First Principle Investigation of Interlayer Interaction, Stacking Order and Layer Number Dependent Structural and Electronic Properties of Multi-Layered Boron Nitride (BN) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Layered Boron-Nitride (BN) consist of covalent in-plane bonding with van der Waals (vdW) interlayer interactions between layers. In this study, stacking order, interlayer-interaction and layer number dependent structural and electronic properties of multi-layered BN were studied using Density Functional Theory (DFT). The lattice constant, equilibrium interlayer distance and energy band structures for different interlayer distances and the number of layers were computed. The calculated result indicates that interlayer interaction and stacking order in a multi-layer limit could impact on its structural and electronic properties. In addition to this, the calculated energy band structure for the increasing number of layers indicates that as the number of layers increases the bandgap decreases. However, the nature of the bandgap remains direct. Moreover, the Partial Density of State (PDOS) analysis reveals that many contributions of states in the vicinity of Fermi level derived from Boron p-orbital followed by nitrogen p-orbital. The findings are bases for experimentalist to control structural and electronic properties of layered materials by manipulating its stacking patterns and layer numbers.
Keywords: Density functional theory; Interlayer interaction; Stacking order; Layer number; Energy band structure